Education for environmental literacy : towards participatory action research in the secondary school science curriculum in Lesotho - Mokuku, Tsepo (Rhodes University, Faculty of Education, Department of Education, 2000)
The dependency of educators in Lesotho on externally developed curriculum theories and concepts is fundamental to issues of relevance of the school curricula. This study set out to develop the meaning of environmental literacy in the context of three secondary schools and to explore appropriate teaching methods for the development of this concept in the science curriculum. The participatory action research process involved a team of four science teachers, including the researcher, in partnership with an environmental centre. We progressively developed the meamng of environmental literacy by monitoring teaching innovations in the classroom, holding meetings and workshops and attending conferences where we shared classroom findings and reflected on our emerging understandings based on classroom experiences. Data collection involved: audio-recording of classroom lessons, interviews with teachers and students, audio-visual recording, classroom observations and students' questionnaires. The research process made apparent the complex nature of the process of clarifying and developing environmental literacy in this context. Classroom actiyities planned to inform the team's understanding of the meaning of environmental literacy and develop appropriate teaching methods encountered constraints associated with the education system and the legacy of colonialism. These contextual constraints crystallised the need for the education system to be transformed in order to make schools more conducive environments for the gevelopment of students' environmental literacy. While initially teachers were reluctant to engage in critical reflection, the research process did encourage the team to revise and expand their understandings of both environmental literacy in the science classroom, and the action research itself. The emerging meaning of environmental literacy in this context and how it may be developed among students does not involve a definition with prescriptive, effective teaching methods, but provides insights and understandings gained by the participants in their engagement with a reflective process of reconslructing meaning. I have come to understand environmental literacy during the study to be a process that should draw strongly on the local knowledge and understandings into the science curriculum, through participatory process-based curriculum development models.
Keywords: Environmental education -- Lesotho; Science -- Study and teaching (Secondary) -- Lesotho